Incidence of Metallo Beta-Lactamase Producing Pseudomonas Aeruginosa in Diabetes and Cancer Patients - Henna Khalid, Mariam Riaz, Sara Najeeb, Nazma Kiran (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Nosocomial infections could be caused by strains of metallo-beta-lactamase (MBL)-producing Pseudomonas aeruginosa. Public health issues are associated with Pseudomonas aeruginosa, a major healthcare associated pathogen. However, the prevalence of Pseudomonas aeruginosa in diabetes and cancer patients are yet to be determined. The present study aimed to determine the prevalence of metallo-beta-lactamase (MBL)-producing Pseudomonas aeruginosa in diabetes and cancer patients. Methodology: This cross-sectional study was conducted on 186 P. aeruginosa isolates taken from diabetes and cancer patient’s samples in the Department of Pathology, Ayub Teaching Hospital Abbottabad from March 2017 to February 2021. Clinical outcome and incidence of P. aeruginosa in diabetes and cancer patients have been investigated. A CLSI-guideline-based susceptibility test was performed on these isolates to assess their susceptibility to anti-pseudomonal drugs. A disc potentiation test using imipenem and meropenem discs impregnated with EDTA was performed on them to screen for MBL production. SPSS version 26 was used for data analysis. Results: Out of 186 P. aeruginosa isolates, about 54 (29%) had shown resistance to carbapenems (imipenem and meropenem) and MBL producers were found in 42 (22.6%) isolates. Out of 42 MBL producer isolates, the prevalence of diabetes, cancer, and both diabetes and cancer were found in 30 (71.4%), 8 (19%), and 4 (9.5%) respectively. The combine therapy of amikacin, piperacillin with tazobactam, and colistin were responded by 7 (16.7%) whereas 35 (83.3%) patients responded to the combination therapy of gatifloxacin, amikacin, and piperacillin with tazobactam. Conclusion: The present study found that the prevalence of MBLs was 22.6%. Consequently, It has been reported that the rapid dissemination of MBL producers makes surveillance studies a priority, as well as the proper selection of antibiotics, especially carbapenems. MDR P. aeruginosa infections may be treated with polymyxins, aaminoglycoside or fluoroquinolone molecules without therapeutic MBL inhibitors. Keywords: Metallo-beta-lactamase-producing, Pseudomonas aeruginosa, diabetes, Cancer patients